REVIEW OF STRUCTURAL AND FUNCTIONAL CHARACTERISTICS OF MODERN TRANSPORTATION AND LOGISTICS ENTERPRISES - Razumova, Kateryna; Selishchev, Serhii; Klymenko, Viktoriia; Novalska, Nadiya; Dokienko, Larisa (Science-based technologies, 2025)
transport and logistics industry in the economy of Ukraine through comparative analysis; the structural and functional features of the activities of a modern transport and logistics enterprise in the form of transport and logistics centers, which arose during evolutionary transformations in the transport services market and provide an opportunity to receive high-quality transport services not only in terms of delivering goods "just in time" to the destination, but also covering a whole range of related services, are considered; analyzed the factors of location of transport and logistics infrastructure enterprises and factors that restrain the development and efficiency of transport logistics in general, as well as its profile companies, in particular. The purpose of the article is to study the state of transport and logistics enterprises of Ukraine at the present stage, to identify factors necessary for the further promising development of transport logistics, as one of the important economic sectors of today. The structural and functional features of the activities of a modern transport and logistics enterprise are the object of research of the proposed article. The author analyzed the structure of enterprises in the logistics industry and the effectiveness of its improvement; used a comparative analysis of factors restraining the development of transport logistics and other sectors of the economy in modern conditions. It was determined that the policy of the transport and logistics industry should be aimed at stabilizing the processes of reducing transit transportation, which arose as a result of active military operations in the country, creating new regional projects of transport and logistics centers, and attracting various levels of investment for more effective development of the main international corridors and large transport and logistics centers. It is necessary to radically change the structure of transport and logistics companies, the main part of which are freight forwarding companies. A high level of transport and logistics services using advanced IT systems and international experience in modern realities is provided by transport and logistics centers, the development of which in Ukraine is taking place at a rather slow pace, which, in turn, reduces the demand for domestic transport and logistics services and increases the number of international logistics operators that are actively operating in the country. It is the transport and logistics centers that can include a significant number of enterprises specializing in the performance of a specific type of logistics and related services. Such centers can be involved in global supply chains.